Empirical analysis of B2B electronic purchasing usage by firms : a post-adoption model integrating trust. - Tan, Jennifer Puay Leng. (2008)
There is a current gap in research of new technologies in the B2B electronic commerce environment. We propose and empirically test a predictive model of B2B electronic purchasing usage by firms. This model integrates the multi-dimensional construct of trust, which recent electronic commerce research propose to be a key factor in electronic commerce participation.